PERAN KEPEMIMPINAN KEPALA SEKOLAH MEMODERASI PENGARUH KOMITMEN SEKOLAH DAN KOMPETENSIGURU TERHADAP KINERJAGURU (Studi pada Guru-Guru PNSSD di KecamatanBawangKabupaten Batang) (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study was investigated about the role of school culture moderated influence commitment and competence on teacher performance. Specifically, this study examine and analisys whether the role of school culture moderated influence commitment and competence on teacher performance. The contribution of this study is explain and explore the previous research about the influence school culture, commitment, and competence on teacher performance. The study population was a primary school teacher in UPT Bawang District of Batang Regency. This research data is the primary data collected directly from the respondents to the questionnaire. This researc method approach with computer software SPSS for windows version 16. The method of data analisys using moderation regression analisys (MRA) type quasi moderator. The result of this study shows an interesting empirical conditions to be further investigated as follow; the cometence was significant influence to teacher performance, but after interacting with school culture, the role school culture to weaken influence of competence on teacher performance. Keyword: commitment, competence, school culture, teacher performance